2017
DOI: 10.7717/peerj.3057
|View full text |Cite
|
Sign up to set email alerts
|

When moult overlaps migration: moult-related changes in plasma biochemistry of migrating common snipe

Abstract: Moult of feathers entails considerable physiological and energetic costs to an avian organism. Even under favourable feeding conditions, endogenous body stores and energy reserves of moulting birds are usually severely depleted. Thus, most species of birds separate moult from other energy-demanding activities, such as migration or reproduction. Common snipe Gallinago gallinago is an exception, as during the first autumn migration many young snipe initiate the post-juvenile moult, which includes replacement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Dietary protein supply is crucial for the maintenance of body form and function because there is no storage form of protein in the body, and this implies that protein limitation may lead to breakdown of fat-free tissues (Krieger et al, 2006), including skeletal muscles and digestive organs (Piersma & Gill, 1998). Annual moult involves substantial tissue replacement and so moult may exploit tissue proteins if dietary supplies are limited (Podlaszczuk, Włodarczyk, Janiszewski, Kaczmarek, & Minias, 2017), especially because feather growth occurs during the post-absorptive state (Chen et al, 2015). However, although feather keratin requires high amounts of sulphur amino acids (methionine and cysteine) to synthesize (Murphy & King, 1984), the 'actual nutrient requirements' of moult are unclear because moult may proceed with limited nutrients or under a wide variety of diets (Murphy & King, 1992), albeit resulting in poor quality feathers or protraction of the moulting period (Murphy, King, & Lu, 1988;Vágási, Pap, & Barta, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary protein supply is crucial for the maintenance of body form and function because there is no storage form of protein in the body, and this implies that protein limitation may lead to breakdown of fat-free tissues (Krieger et al, 2006), including skeletal muscles and digestive organs (Piersma & Gill, 1998). Annual moult involves substantial tissue replacement and so moult may exploit tissue proteins if dietary supplies are limited (Podlaszczuk, Włodarczyk, Janiszewski, Kaczmarek, & Minias, 2017), especially because feather growth occurs during the post-absorptive state (Chen et al, 2015). However, although feather keratin requires high amounts of sulphur amino acids (methionine and cysteine) to synthesize (Murphy & King, 1984), the 'actual nutrient requirements' of moult are unclear because moult may proceed with limited nutrients or under a wide variety of diets (Murphy & King, 1992), albeit resulting in poor quality feathers or protraction of the moulting period (Murphy, King, & Lu, 1988;Vágási, Pap, & Barta, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Haematological parameters are among the most direct indicators of physiological condition and are recently widely used in field and experimental studies of birds and mammals ( Norte et al , 2008 ; Johnstone et al , 2015 ; Podlaszczuk et al 2017 ; Kaliński et al 2016 , 2017a ). The concentration of haemoglobin is positively related to the physiological condition of nestling altricial birds, which depend on the quantity and quality of food delivered to them by parents ( Lill et al , 2013 ; Minias, 2015 ; Kaliński et al , 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Klaassen 1995;Guillemette et al 2007), the process of moult in the Common Snipe has been shown to be energetically costly. Young snipe were found to have lost more than 50% of their fat reserves during the postjuvenile moult (Minias et al 2010b), and depletion of endogenous fat was accompanied by a significant decrease in plasma concentrations of triglycerides during the advanced stage of moult (Podlaszczuk et al 2017). However, it remains unknown whether overlapping costs of moult and migration produce elevated levels of organismal stress in species such as the Common Snipe.…”
Section: Introductionmentioning
confidence: 99%